2010
DOI: 10.1371/journal.pgen.1000980
|View full text |Cite
|
Sign up to set email alerts
|

Cushing's Syndrome and Fetal Features Resurgence in Adrenal Cortex–Specific Prkar1a Knockout Mice

Abstract: Carney complex (CNC) is an inherited neoplasia syndrome with endocrine overactivity. Its most frequent endocrine manifestation is primary pigmented nodular adrenocortical disease (PPNAD), a bilateral adrenocortical hyperplasia causing pituitary-independent Cushing's syndrome. Inactivating mutations in PRKAR1A, a gene encoding the type 1 α-regulatory subunit (R1α) of the cAMP–dependent protein kinase (PKA) have been found in 80% of CNC patients with Cushing's syndrome. To demonstrate the implication of R1α loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 60 publications
5
103
0
2
Order By: Relevance
“…We previously showed that adrenal-specific ablation of Prkar1a using the Akr1b7-Cre driver in mice (AdKO mice) resulted in ACTH-independent Cushing's syndrome and centrifugal expansion of large fetal-like cells from the innermost cortex (19). Because the Akr1b7-Cre driver targets recombination to both the definitive (adult) and transient (fetal or X-zone) cortices (24), the origin of these cells has remained elusive.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously showed that adrenal-specific ablation of Prkar1a using the Akr1b7-Cre driver in mice (AdKO mice) resulted in ACTH-independent Cushing's syndrome and centrifugal expansion of large fetal-like cells from the innermost cortex (19). Because the Akr1b7-Cre driver targets recombination to both the definitive (adult) and transient (fetal or X-zone) cortices (24), the origin of these cells has remained elusive.…”
Section: Resultsmentioning
confidence: 99%
“…Gain-and loss-of-function models have shown that the RSPO/WNT/β-catenin pathway is a driver of zG identity, a repressor of zF identity, and has tumorigenic activity when constitutively activated (14)(15)(16)(17). Reciprocally, constitutive activation of cAMP/PKA signaling was shown to inhibit zG fate, trigger zF identity, and counteract β-catenin-induced tumorigenesis (18,19). Decreased PKA signaling, resulting from mutations in the ACTH receptor MC2R, or in its coreceptor MRAP, are associated with cortical atrophy, altered zF differentiation, and, yet, intact zG (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hyperplastic adrenal cortex in the vicinity of the pheochromocytoma, contrasting with atrophy of the residual cortex, is in favor of paracrine regulation of adrenocortical hyperplasia cells by pheochromocyte secretory products. Similarly, the preferential localization of adrenocortical micronodules close to the corticomedullary junction observed in adrenal from patients with primary pigmented nodular adrenocortical disease (PPNAD) with inactivating mutation of PRKAR1A or in mouse models of PPNAD (54,55) is consistent with cortical-medullary interactions. Intercellular communication between chromaffin and steroidogenic cells is supposed to be more intense in corticomedullary mixed tumors, as these well-circumscribed tumors are composed of an intimately admixed population of adrenocortical cells and pheochromocytes (56,57,58,59).…”
Section: Sources Of Paracrine Regulatory Factors In Adrenocortical Nementioning
confidence: 70%
“…In the adrenocortical cell line H295R, PRKAR1A inactivation inhibits TGFb-induced apoptosis through a decrease in SMAD3 expression, which plays a major role in TGFb signaling (229). This mechanism may be involved in adrenocortical hyperplasia and resistance of adrenocortical cells to apoptosis observed in PPNAD (55).…”
Section: Factorsmentioning
confidence: 99%